Развитие исследовательской компетентности будущих учителей физики на основе STEM-подхода (SCIENCE and SOCIETY, 2025)
This article explores the role of the STEM approach in developing the research competence of future physics teachers. Through interdisciplinary integration and the use of modern educational technologies, the study demonstrates how practical and project-based learning activities enhance students’ analytical and experimental skills. The work provides specific examples of experimental projects based on physics and technology, emphasizing the importance of fostering scientific thinking and the ability to solve real-world problems in teacher education.